Structuralism and Law - Alzamora Valdez, Mario (1974)
The aim of this paper is to analyze the possibility of understanding law from the perspective of structuralism. For this purpose, the different structuralist expressions and doctrines are examined to determine their influence on the sciences. In this context, the concept of legal structuralism is developed in order to evaluate the feasibility of studying law from this approach. In this way, by defining structuralism from different approaches, it is concluded that it does not fit completely with law, since it is limited to certain areas and its study would be incomplete.